Hubungan Antara Pola Tutupan Lahan Terbangun Dan Laju Infiltrasi Air Hujan - R. BELA, Krisantos; SERAN, Engelbertha N. BRIA; NAIKOFI, Mauritius I.R.; DA COSTA, Don Gaspar Noesaku (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
Kupang City is an area in Indonesia which has a relatively low number of rainy days. This causes the supply of clean water or drinking water in Kupang City to decrease. The high infiltration rate not only increases the amount of water stored in the soil, but also reduces flooding and erosion caused by run off. This study aims to model the relationship between infiltration and discharge capability for each type of samples land by using linear regression method. For this reason, a water absorption test was conducted on the built up area based on the infiltration rate. The results of experiments and calculations using linear regression shown that area often received heavy load such as vehichles had lower infiltration rate leading to slow inundation height decrease. While areas rarely received heavy load had higher infiltration rate. Even though the difference is only around 2-3 cm / 5 minutes, it indicates that the availability of open areas is still needed to support the implementation of the zero run-off model in urban built areas